Redox-active conductive metal-organic framework with high lithium capacities at low temperatures - Kumar, Yogendra; Kim, Tae Hyeong; Subiyanto, Iyan; Devina, Winda; Byun, Segi; Nandy, Subhajit; Chae, Keun Hwa; Lim, Suim; Kim, Bumjin; Kang, Sanghui; Han, Seong Ok; Yim, Kanghoon; et al. (Royal Society of Chemistry, 2024)
Lithium-ion batteries suffer from reduced capacities and stabilities at low temperature due to poor Li intercalation to the graphite anode. Graphite has a high activation energy (similar to 0.6 eV) to accommodate Li ions, resulting in a substantial capacity drop at low temperatures. Additionally, it can induce the formation of Li dendrites on the surface of graphite. To address this issue, we designed and synthesized a redox-active fluorothianthrene-based MOF (SKIER-5). SKIER-5, which undergoes three-electron redox reactions resulting from the fluorothianthrene-based organic ligand and Ni, exhibited excellent electrochemical performance at various temperatures when used as an anode. In particular, the discharge capacities of SKIER-5 were significantly higher than those of commercial graphite at low temperatures (<-10 degrees C) because of the lower activation energy (similar to 0.23 eV) for charge transfer. Moreover, it maintained stability when cycled at -20 degrees C, highlighting its potential as a promising anode material in low-temperature environments.